Juan Nicasio Gallego en el imaginario nacional (1831-1879) - Eduardo Fernández López (Cuadernos de Ilustración y Romanticismo)
Juan Nicasio Gallego was a priest, poet and politician who displayed an intense activity during the first half of the 19th century. He became part of the cultural and literary circles of the Court from the first years of his life, something that in the long run would earn him great friendships who watched over his life when power turned his back on him. Deputy substitute for Zamora in the Cortes de Cádiz of 1812, he became one of the most important deputies, and he argued more and fought for the first Spanish constitution to go ahead. He would fall to misfortune, be persecuted and imprisoned by absolutism after Ferdinand VII in 1814, and return to exile in France for a few months after the second Fernandina restoration. Meanwhile he would dedicate his life to the poetic creation and to help young writers who found in him a protector and a friend. He would obtain real pardon and recover his privileges within the Court in the final part of his life, and at that moment he would be recognized as a great poet and a lofty Perpetual Secretary of the Royal Spanish Academy among other posts.